ANALISIS PENDAPATAN PADI (Oryza sativa. L) VARIETAS KARANG DUKUH DI KECAMATAN TAMBAN CATUR KABUPATEN KAPUAS KALIMANTAN TENGAH - Ari Jumadi Kirnadi; Bagio Mujiono (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2016)
This study aims to determine the financial aspects in the implementation of karang dukuh varieties of rice farming in the district of Kapuas Tamban Catur, which include costs of farming, receipts, income and the feasibility of farming operation. This study uses a survey in four villages of seven villages in the district of Kapuas Tamban Catur. The sampling is done by using purposive sampling method against 35 people who grow rice varieties of Karang Dukuh. As a variable in this study is the explicit costs, implicit costs, the total cost and the feasibility of Karang dukuh rice farming. The results showed that the average cost of an explicit (per ha) amounted to Rp 4,996,567,- while the costs are not incurred (per ha) amounting to Rp 2,211,458,- thus the average total cost per ha is Rp 7,208,025, - Acceptance average of Karang Dukuh  rice farming in the district amounting to Rp 16,770,914,- per ha. Revenues derived from the difference between the reception with iaya explicit, which amounting to Rp 11,774,347,- per ha. Judging from the feasibility shows Karang Dukuh rice farming in the district tamban catur of 2.3 and is therefore worth the effort. Keywords: Income, Karang dukuh rice